Как решить (2 5/6-3 4/5*1 1/9): (-3,75)

qwertyroom qwertyroom    2   02.09.2019 15:30    0

Ответы
MrWolf1244 MrWolf1244  06.10.2020 12:34
(2 5/6 - 3 4/5 * 1 1/9) : (-3,75) = 10/27,

1) 3 4/5 * 1 1/9 = 19/5 * 10/9 = 38/9 = 4 2/9,
2) 2 5/6 - 4 2/9 = 17/6 - 38/9 = 51/18 - 76/18 = -25/18,
3) -25/18 : (-3,75) = 25/18 : 375/100 = 25/18 * 100/375 = 10/27
ПОКАЗАТЬ ОТВЕТЫ
anastasia106444 anastasia106444  06.10.2020 12:34
1) 3 4/5 • 1 1/9 = 19/5 • 10/9 = 38/9 = 4 2/9
2) 2 5/6 - 4 2/9 = 2 15/18 - 4 4/18 = 2 15/18 - 3 22/18 = - 1 7/18
3) - 1 7/18 : ( - 3,75 ) = 25/18 : 15/4 = 20/54 = 10/27
ответ 10/27
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика